Engineering education & practice in Malaysia / Norlida Buniyamin - Buniyamin, Norlida
To choose a topic for my professorial lecture turns out to be quite difficult. I do have many interests, in various areas of research in technical engineering fields and in engineering education, that are interesting and exciting to me. I have indulged myself in these interests and am involve in many areas in both engineering education and in the technical areas of the profession of engineering. In the end, this topic was selected as it could potentially reach many lecturers in the college of engineering that maybe interested in a particular area. With the merger of all engineering faculties in Universiti Teknologi MARA (UiTM), and we are now the College of Engineering, UiTM, I have selected a topic that I hope will be of interest to most of us as an educator and a practitioner in the many technical fields of engineering. In my experience of more than 30 years as an engineering practitioner, I have been active in the areas of Knowledge Management, Robotics & Automation, Biomedical Engineering and Engineering Education. Throughout these years, interest in research in Engineering Education and the development of policies in engineering education have remained with me.